Physiological and perceptual recovery-stress responses to an elite netball tournament - Russell, S.; Simpson, M. J.; Evans, A. G.; Coulter, T. J.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate and explore the relationships between physiological and perceptual recovery and stress responses to elite netball tournament workloads.